Dracula - Stoker, Bram 1847-1912; Claypole, Jonty (London Macmillan Collector's Library, 2016)
'I am Dracula. And I bid you welcome to my house.' He is deathly pale. His fingernails are cut to sharp points. His teeth protrude menacingly from his mouth in clouds of rancid breath. Yet even Count Dracula's unnerving appearance and the frightened reaction of the local peasants fail to warn Jonathan Harker, a young man from England, about his host. Little does Jonathan know that this is a land where babies are snatched for their blood and wolves howl menacingly from the forest, where reality is far more frightening than superstition. What's more, it's going to be up to him to stop the world's most bloodthirsty predator.
"First published by Collector's Library 2003."--Title page verso.
Includes bibliographical references.
Keywords: Dracula -- Count (Fictitious character) -- Juvenile fiction; Vampires -- Juvenile fiction